Mechanical properties study of pseudo-stem banana fiber reinforced epoxy composite - Maleque, Md. Abdul; Belal, F. Y.; Sapuan, S. M. (KFUPM, Saudi Arabia, 2007)
The source of banana fiber is the waste banana trunks or stems which are abundant in many places in the world. Therefore, composites of high–strength pseudo-stem banana woven fabric reinforcement polymer can be used in a broad range of applications. The objective of this paper is to study the tensile, flexural, and impact properties of pseudostem banana fiber reinforced epoxy composites.